Initial analytic quality assessment and method comparison of an immunoassay for adrenocorticotropic hormone measurement in equine samples. (12th January 2016) - Irvine, Katherine L.; Burt, Kay; Hill, Andrew J.; Shaw, Stephanie; Papasouliotis, Kostas
Abstract : Background: Equine pituitary pars intermedia dysfunction (PPID) may be diagnosed by measuring baseline plasma adrenocorticotrophic hormone (ACTH). The Immulite 1000 analyzer uses an automated chemiluminescence enzyme assay, previously validated for measuring equine ACTH. Recently, an automated bench‐top immunoassay analyzer (AIA‐360), designed for analytes in people, became available for veterinary use. Objectives: Objectives were to evaluate analytic performance of the AIA immunoassay for measuring equine ACTH, and compare the results with those obtained by the Immulite. Methods: Adrenocorticotrophic hormone was measured in plasma samples from 52 clinical cases. For the AIA, within‐ and between‐run coefficients of variation (CV) were assessed, linearity and recovery studies performed, and observed total error (TEobs ) calculated. Correlation and agreement between the 2 analyzers were also evaluated. Results: Within‐run and between‐run CV of the AIA ranged from 2.3% to 4% and 3.5% to 8%, respectively. ACTH recoveries ranged from 89.5% to 115.9%. TEobs at 26.5 pg/mL ACTH was 4.1 pg/mL. The ACTH results (median: 25.9 pg/mL; range: 4.3–276.7 pg/mL) with AIA were significantly lower ( P < .0001) than with the Immulite (median: 29.9 pg/mL; range: 10.3–639.0 pg/mL). Correlation between the 2 analyzers was r = 0.882 ( P < .0001), with a significant bias for the AIA of −16 pg/mL. The 2 methods were not identical within inherent imprecision. Conclusion: The AIA is precise for measuring ACTH in horses. Although correlation between the instruments is good, the values obtained by the immunoassays cannot be used interchangeably and should be interpreted using reference intervals established for each analyzer to avoid false negatives. Diagnostic sensitivity and specificity of the AIA‐360 should be evaluated before clinical use.